Non-contact monitoring to support care in acute inpatient mental health - Ndebele, Faith; Wright, Kay; Gandhi, Varsha; Bayley, Daniel (Journal of mental health (Abingdon, England), 2024)
Averting incidents of patient self-harm is an ongoing challenge in acute inpatient mental health settings. Novel technologies that do not require continuous human visual monitoring and that maintain patient privacy may support staff in managing patient safety and intervening proactively to prevent self-harm incidents. To assess the effect of implementing a contact-free vision-based patient monitoring and management (VBPMM) system on the rate of bedroom self-harm incidents. A mixed methods non-randomized controlled before-and-after evaluation was conducted over 24 months on one female and one male acute inpatient mental health ward with the VBPMM system. The rates of bedroom self-harm, and of bedroom ligatures specifically, before and after implementation were investigated using quantitative methods. Qualitative methods were also used to explore the perceived effectiveness of the system and its acceptability. A -44% relative percentage change in bedroom self-harm incidents and a -48% relative percentage change in bedroom ligatures incidents were observed in the observational wards with the VBPMM system. Staff and patient responses gave insights into system acceptability and the ways in which these reductions may have been achieved. The results indicate that using the VBPMM system helped staff to reduce self-harm incidents, including ligatures, in bedrooms.